Physicians’ Perception about the Role of Speech and Language Pathologist in Dysphagia - Faiqa Saleem, Arshad Mehmood Naz, Hunia Kashif, Laraib Ramzan, Fahad Masood, Attaullah Khan Niazi, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Dysphagia is characterised as having trouble digesting food from the mouth to the stomach. It is the sensation of the hindrance of food when it’s passing from the mouth through the oesophagus. Dysphagia can be caused due to or pharyngeal or oesophageal etiologist. Objective: To determine the physician perception about speech-language pathologists' role in dysphagia. Methodology: To achieve this goal, the researcher surveyed physicians including otolaryngologists, neurologist and gastroenterologists about their perception about the involvement of SLP in the management of dysphagia. A cross-sectional survey was conducted in Lahore, Pakistan. Data for the study was collected from the public and private hospitals and clinics by convenient sampling technique. 97 Doctors completed a questionnaire created by the researcher that had two sections, each of which captured the participant's demographics, closed ended questions regarding physician’s perception (15 items). Results: The results depict that 40.2% of physicians thinks that speech and language pathologist rarely become a part of the team when patient reports difficulty during Preparatory and Pharyngeal phase of swallowing with the mean±SD = .92 ± .909. While 37.1% of the physician thinks that SLPs frequently becomes a part of team when patient complaints about voice alternations with the mean±SD = 2.43 ± 1.117, 53.6% of the physician thinks that SLPs frequently becomes a part of team when patient complaints about Drooling with the mean±SD = 2.59 ± .887, 53.6% of the physician thinks that SLPs frequently becomes a part of team when patient complaints about Poor tongue movements with the mean±SD = 2.74 ± .916 , 50.5% of the physician thinks that SLPs frequently becomes a part of team when patient complaints about asymmetrical facial musculature with the mean±SD = 2.97 ± .847. Practical Implication: The field of speech and language pathology has the main domain of dealing with dysphagia patients but the physicians have yet to understand the scope of speech language pathologists and the role they play in the diagnosis and management of dysphagia, this research will serve to point out the gap of knowledge and awareness of the physicians and the areas that need to be addressed to narrow this gap and increase patient care quality. Conclusion: This study concluded that most of the physicians had insufficient knowledge about the involvement of Speech and language pathologist in the multidisciplinary team for the management of dysphagia. Keywords: Speech and language pathologist, Dysphagia, Swallowing disorders, Feeding disorder.